Optimization of the Risk-Based Annual Supervision Work Program to Improve the Quality of Supervision Results at the Balikpapan City Inspectorate - Dyna Evi Septiana; Saipul saipul; Harianti harianti (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
This study analyzes the strategic dimensions that influence the quality of risk-based supervision through a comprehensive examination of three interrelated domains: coordination and governance, human resources, and technology integration. The research employs a descriptive qualitative method supported by analytical visualization using a donut diagram to illustrate the proportional contributions of each domain to supervisory effectiveness. Findings reveal that coordination and governance play a dominant role in ensuring institutional coherence, accountability, and leadership alignment, while human resources emerge as the core determinant of adaptive and ethical audit performance. Technological integration functions as a transformative enabler that strengthens data-driven decision-making and operational transparency within the supervisory framework. The interaction among these three domains demonstrates that the success of risk-based supervision depends on systemic balance rather than isolated reforms. The study concludes that strengthening institutional coordination, investing in professional capacity, and advancing digital infrastructure are essential for building a sustainable, responsive, and accountable supervision system capable of addressing dynamic governance risks.